2020
DOI: 10.3389/fmicb.2019.02908
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological and Medical Aspects of Aspergillus-Derived Mycotoxins Entering the Feed and Food Chain

Abstract: Background: A atoxins are major contaminants of feed used in poultry industry that negatively affect animal and human health. In Ethiopia, previous studies on a atoxins mainly considered cattle feed and milk, but scarce information exists for poultry feeds. Method: The aim of this study was to determine the burden of a atoxin in poultry feed in bishoftu.Cross sectional study was conducted from December, 2018 to May, 2019and 33 compound poultry feed samples were randomly collected from chicken rearing villages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(125 citation statements)
references
References 205 publications
2
103
0
3
Order By: Relevance
“…The transfer rate observed in our trial is in agreement with those cited (1% to 6% in dairy cows) by the European Food Safety Authority [8]. The inverse relationship between transfer and AFB 1 intake could be related to the biotransformation processes of these mycotoxins in animal tissues [1]. Kutz et al [38] reported that supplementation of yeast cells at 0.50% of DM in feed containing 100.0 µg of AFB 1 /kg decreased AFM 1 in milk from dairy cows.…”
Section: Afm 1 Concentration In Milksupporting
confidence: 92%
See 2 more Smart Citations
“…The transfer rate observed in our trial is in agreement with those cited (1% to 6% in dairy cows) by the European Food Safety Authority [8]. The inverse relationship between transfer and AFB 1 intake could be related to the biotransformation processes of these mycotoxins in animal tissues [1]. Kutz et al [38] reported that supplementation of yeast cells at 0.50% of DM in feed containing 100.0 µg of AFB 1 /kg decreased AFM 1 in milk from dairy cows.…”
Section: Afm 1 Concentration In Milksupporting
confidence: 92%
“…The transfer of AFM 1 in milk was calculated as the ratio between the AFM 1 excreted in milk (µg/L) and the AFB 1 intake (µg/kg) at the time when the toxin output in milk reached a steady state. This value was used to calculate the percentage of ingested AFB 1 excreted daily in milk as AFM 1 :Transfer (%) = (Total AFM 1 excreted (µg/day)/AFB 1 ingested (µg/day)) × 100.…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Aflatoxins have toxic, carcinogenic, mutagenic and teratogenic effects in the humans and animals; with predilection to the liver (Milicevic et al 2015;Zain 2011). Aflatoxin-contamination along the animal feed chain, is not generally given attention especially in developing countries, however, it contributes to exposure of the human consumers to contaminated products (Akande et al 2006;Ráduly et al 2020). Aflatoxins are associated with economic impacts including increased mortality of farm animals, lowered livestock productivity, increased veterinary costs and challenges in disposal of contaminated feeds and feed ingredients (Akande et al 2006;Zain 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence of high levels of aflatoxins in animal feeds (Kaaya et al 2000). Information on aflatoxin levels in poultry feeds remains scarce; yet contaminated animal products are a major source of exposure to the human consumers (Ráduly et al 2020). Apart from institution of various control strategies, successful management of aflatoxins requires awareness by the various stakeholders.…”
Section: Introductionmentioning
confidence: 99%